Desarrollo de una iniciativa de comunicación educativa en entornos digitales para la carrera de comunicación social. - Zambrano Macías, José Rolando (2016)
Digital communication has played a very important role since the beginning of the Internet, better still with the web 2.0, so here the research essentially addressed the factors that affect the university environment for the application of digital communication. The term web 2.0 makes relevance to the progress that communication had at the root of its advent, providing another way to communicate to users of the web. This article explains the concept of web 2.0, from the change that was generated since its appearance back in 2004, when the social form has come to change the form of communication between people. For this research, a quantitative approach was applied that helped to find reliable results for this work, since the survey was used as a data collection instrument. In addition, a description of the characteristics of the web 2.0 was developed, which allowed a better technical performance of the same, analyzed the part of the interpersonal communication considered to the digital plane.